Novel oil extraction methods in food industry: A review (Journal of Oilseed Brassica, 2026)
Many fruits and cereals contain essential oils which are attaining importance in food, drug, and cosmetic industries owing to their desirability, and nutraceutical properties. Soxhlet extraction is the method used for isolation of oil from plant material. Usually, plant materials are subjected to mechanical shear using expellers to release the volatiles in virgin state. A new method of extraction has been solvent extraction involving use of polar solvents. The disadvantage with the process is the use of hazardous, and flammable liquid organic solvents, potentially toxic emission during extraction, non-selective extraction, and time consuming. In order to obtain a good yield from extraction as well as to prevent the uses of volatiles, correct alternative of solvent is very important. Novel extraction methods like ultra sound extraction, microwave assisted extraction, and supercritical fluid extraction has been successfully employed for extraction of oils with higher yield, and better physiochemical, and functional properties. This article reviews the recent work on extraction using novel methods like ultra sound extraction, microwave assisted extraction, and supercritical fluid extraction.